Current Status of Pyrethroids Resistance in Aedes aegypti (Culicidae: Diptera) in Lahore District, Pakistan: A Novel Mechanistic Insight. Issue 6 (3rd August 2021) - Nawaz, Saira; Tahir, Hafiz Muhammad; Asif Mahmood, Muhammad; Summer, Muhammad; Ali, Shaukat; Ali, Aamir; Gormani, Ali Haidar
Abstract: Aedes aegypti (Linnaeus, 1762) is a major vector responsible for dengue transmission. Insecticides are being used as the most effective tool to control vector populations in Lahore, Pakistan. Control of Ae. aegypti is threatened by the development of resistance against insecticides. The current status of insecticide resistance was evaluated against pyrethroids (deltamethrin, cypermethrin, and lambda-cyhalothrin) in different populations of Lahore (Model Town, Mishri Shah, Sadar Cantt, Walton, and Valencia). The susceptibility of the larval and adult populations was tested following the standard WHO guidelines. Moderate to high levels of resistance were found against pyrethroids in the larval (RR50 : 3.6–27.2 and RR90 : 5–90) and adult populations (percentage mortality < 98%). Biochemical assays revealed a statistically significant increase in the enzyme level in all field populations compared to the laboratory strain. The value of esterase was one-fold higher, monooxygenase was 3.9- to 4.7-fold higher, and glutathione S-transferases was 1.9- to 2.6-fold higher in field populations compared to the laboratory strain. These results depict the presence of resistance against deltamethrin, cypermethrin, and lambda-cyhalothrin in field populations of Lahore mediated by metabolic enzymes i.e. esterases, monooxygenases, and glutathione S-transferase.